Penerapan Student Center Learning Pada Peserta Didik Kelas 2 SD Muhammadiyah 14 Surakarta Terhadap Pemahaman Konsep Matematis - Jumadi, Jumadi (Universitas Sebelas Maret, 2022)
This study aims to provide an overview of the implementation of learning approaches in SD Muhammadiyah 14 Surakarta during the Teacher Profession Education (PPG). The study was conducted using descriptive qualitative methods. Data collection was carried out by documentation, observation, and interviews. Then, data analysis used the Miles and Huberman Interactive Model through the stages of: collecting data, reducing data, presenting data and conclusions. The researcher conducted learning for class 2 students at SD Muhammadiyah 14 Surakarta using a student centered learning (SCL) approach. The methods applied were discussion, learning by playing, and practice questions. The results of the study showed that the implementation of SCL can significantly increase student participation in learning and improve understanding of a matematic concept. Class 2 students who participated in the SCL approach showed improvement in self-motivation, cooperation, and problem solving.